THE CODING AND INTERPRETATION OF ART. 12 OF THE CRIMINAL CODE AS A LIMIT TO THE SYSTEMATIC EROSION OF THE CRIMINAL LEGAL ORDINANCE - Borges de Albuquerque Mello, Sebástian (2022)
This article, in a simple homage to René Ariel Dotti, aims to highlight the expansion of Brazilian Criminal Law, especially with regard to extravagant laws and, above all, legal microsystems, which tend, in the hermeneutic process, to distance themselves from the criminal principles contained in the Criminal Code. Hence, the need for a systematic unity of criminal legislation is analyzed, based on the codified criminal principles and the interpretation of art. 12 of the Penal Code in the hermeneutics of the norms contained in the legal microsystems, assuming that the penal principles contained in the Penal Code occupy a prominent place in the legal system. Thus, in this work is applied the hypothetical-deductive method, which is guided by theoretical analysis.